Becoming numerate: enduring theories, recent research, and current issues. Issue 1 (2nd January 2019) - Westwood, Peter
ABSTRACT: The author provides an overview of several theories of numeracy acquisition that, despite criticisms, have withstood the passage of time and continue to influence policy and practices in schools. These are followed by a brief review of some recent research in the domain of numeracy learning and teaching. The article ends with some of the current issues that are (or should be) receiving attention.